Sistem Pendidikan di Australia - Nadia Nauli; Mislaini Mislaini; Sila Angraini (Pusat Riset dan Inovasi Nasional, 2025)
Australia's education system reflects the long history and development of its diverse society. Since the arrival of British colonialists in 1788, Australia has undergone a significant transformation, from a colony to an independent country with a strong identity. The education system in Australia consists of preschool, primary, secondary and tertiary education, and is equipped with various vocational education institutions. Even though Australia is known to have a high-quality education system, there are several problems it faces, such as unequal access to education among indigenous communities, challenges in integrating international students, and issues of unequal funding between regions. Education policy in Australia focuses on improving the quality of education through a variety of initiatives, including teacher skills enhancement programs, inclusive curriculum development, and improving educational facilities. The government is also trying to overcome the problem of inequality by implementing policies that support access to education for all levels of society. Thus, despite facing various challenges, the Australian education system continues to adapt and develop to meet the needs of a dynamic society.